The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s12920-019-0649-6
|View full text |Cite
|
Sign up to set email alerts
|

MEG3 promotes proliferation and inhibits apoptosis in osteoarthritis chondrocytes by miR-361-5p/FOXO1 axis

Abstract: Background: This study aimed to investigate the role of long non-coding RNA (lncRNA) maternally expressed 3 (MEG3) and related molecular mechanisms, in osteoarthritis (OA). Methods: Cartilage tissues of OA patients and healthy volunteers were isolated and cultured. After transfection with the appropriate constructs, chondrocytes were classified into Blank, pcDNA3.1-NC, pcDNA3.1-MEG3, si-NC, si-MEG3, pcDNA3.1-NC + mimics NC, pcDNA3.1-MEG3 + mimics NC, pcDNA3.1-NC + miR-361-5p mimics and pcDNA3.1-MEG3 + miR-361-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 38 publications
(35 reference statements)
1
20
0
Order By: Relevance
“…The numbers of GST genes identified in these four species basically conform to their genome ploidy, which indicates that the GST gene family was conserved during the process of polyploidization. In a recent study, the GST gene family in common wheat was divided into eight classes [ 49 ], but there is evidence that the GST gene family also includes the OMEGA and MAPEG classes in plants [ 1 , 50 , 51 ]. To accurately identify the GST genes in common wheat and its relatives, we updated the classification of the GST genes and largely expanded the membership of this gene family.…”
Section: Discussionmentioning
confidence: 99%
“…The numbers of GST genes identified in these four species basically conform to their genome ploidy, which indicates that the GST gene family was conserved during the process of polyploidization. In a recent study, the GST gene family in common wheat was divided into eight classes [ 49 ], but there is evidence that the GST gene family also includes the OMEGA and MAPEG classes in plants [ 1 , 50 , 51 ]. To accurately identify the GST genes in common wheat and its relatives, we updated the classification of the GST genes and largely expanded the membership of this gene family.…”
Section: Discussionmentioning
confidence: 99%
“…It is a human homologue of mouse maternally imprinted gene trap locus 2 ( Glt2 ), which was first discovered by Miyoshi et al 123 in 2000. MEG3 has been reported in previous studies to reduce ECM degradation in OA chondrocytes, 43 , 44 and the interaction between MEG3 and SRY-associated high mobility protein-2 ( SOX2 ) induces the expression of BMP4 to promote osteogenic differentiation of bone marrow mesenchymal stem cells. 124 In addition, other studies have pointed out that overexpression of MEG3 leads to downregulation of the serine/threonine-specific protein kinase (known as protein kinase B (AKT)) signalling pathway in breast cancer, and the AKT signalling pathway plays a key role in the growth, invasion, and angiogenesis of breast cancer cells.…”
Section: Introductionmentioning
confidence: 98%
“…Chen et al 44 found that MEG3 , as a ceRNA of miR-93 , can promote the expression of transforming growth factor β receptor 2 ( TGFBR2 ), and then activate the TGF-β signalling pathway to reduce ECM degradation. In another study also aimed at MEG3 , Wang et al 43 found that MEG3 inhibits ECM degradation through the miR-361-5p/FOXO1 axis. The expression of MEG3 in human OA chondrocytes was downregulated, while overexpression of MEG3 significantly downregulated the expression of miR-93 and miR-361-5p , inhibiting the expression of MMP-13 and ADAMTS-5 which thus reduced degradation of the ECM.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations